"Hartnell's time machine" reprise: Further implications of zinc, lead and copper in the thumbnail of a Franklin expedition crewmember. (June 2017) - Millar, Keith; Bowman, Adrian W.
Abstract: Christensen et al. (2016) have described the application of synchrotron micro-X-ray fluorescence mapping, stable isotopic analysis and laser-ablation inductively-coupled plasma mass spectrometry to provide a unique and dynamic time scale of the concentration of metals in the thumbnail of John Hartnell who was a member of the 1845 British Royal Naval "Franklin expedition" which met a fatal end in the Arctic. Their finding of low levels of lead and zinc in Hartnell's thumbnail has questioned the supposed lead-poisoning of the crew and introduced a new hypothesis that zinc deficiency contributed to the loss of the expedition. It is proposed here that their innovative and intriguing hypothesis might be considered cautiously in light of uncertainty as to the reliability of nail as a biomarker of zinc deficiency and calculations that the Royal Navy's provisioning of its Arctic ships would have provided adequate dietary zinc. Whilst there may be difficulty in interpreting the absolute levels of zinc in the nail, the change in the levels over time may provide unique insights. It is agreed that exponential increases in levels of zinc, copper and lead seen in the weeks prior to Hartnell's death from pulmonary tuberculosis might reflect endogenous release of the metals due to tissue catabolism. It is further proposed that the increase in those metals also reflects the administration by the expedition's surgeons of lead, zinc and copper-containing medications which were widely used to relieve the distressing symptoms of tubercular disease. Highlights: Evidence that zinc deficiency contributed to the loss of the Franklin expedition is questioned. Absolute levels of zinc in human nail are not reliable biomarkers of zinc deficiency. Changes in levels of zinc, copper and lead over time, rather than absolute levels, provide insight. Medical intervention may explain exponential rises in levels of the metals prior to death.